KARAKTERISASI MORFOLOGI DAN ANALISIS PROKSIMAT JAGUNG (Zea mays, L.) VARIETAS MOMALA GORONTALO - Rizal Suleman; Novri Youla Kandowangko; Aryati Abdul (Jambura Edu Biosfer Journal, 2019)
Research aimed to find out morphological characteristics and proximate analysis of Momala Gorontalo corn (Zea mays, L.) variety. The research applied observation method by doing observation towards Momala Gorontalo corn variety. The data analysis used quantitative descriptive analysis. The morphology characteristics of Momala Gorontalo corn were average plant height was 146.47 cm; average cob height was 73.88 cm; average stem perimeter was 8.46 cm; average leaves number was 12; average leaves strand was 86.59 cm; average leaves midrib was 16.25 cm; average leaves strand width was 8.71 cm; average leaves strand direction was a bit curving; average axilla corner was 39,950; average leaves tip shape was sharp; at grain was 5,86%; at corn hair was 83,76%. Average cob length was 12,58 cm; average cob diameter was 3,34 cm; average cob weight with corn husk was 88,58 g, average cob weight without corn husk was 60,74 g, average seeds number per line was 20, and weight of 1000 grains was 272 g. The proximate analysis of Momala Gorontalo corn for moisture content was 14,82 ± 0,04%; ash content was 1,35 ± 0,01%; crude protein content was 11,51 ± 0,24%; crude fat content was 4,62 ± 0,48%; carbohydrate content was 67,68 ± 0,67%; value of Nitrogen Free Extract (BETN) was 58,36 ± 0,93% and value of metabolic energy was 2886,25 ± 14,68 Kkal/100 g